Jakob Christmann’s (d. 1613) Ottoman letter of 1589 to the Turkish Paulus aka Paul Willich - Çelik, Hülya (Keshif, 2024)
Jakob Christmann’s (d. 1613) Ottoman letter of 1589 to the Turkish Paulus aka Paul Willich